Regulation of pain by neuro-immune interactions between macrophages and nociceptor sensory neurons. (June 2020) - Chen, Ouyang; Donnelly, Christopher R; Ji, Ru-Rong
Highlights: Macrophages induce pain via pro-inflammatory cytokines that activate nociceptors. Nociceptor neurons activate local macrophages via TLR signaling and CCL2 production. Macrophages have bilateral interactions with nociceptors via miRNAs. Macrophages resolve pain via IL-10 that inhibits nociceptor sensitization. Macrophages produce SPM and respond to SPM to resolve inflammation and pain. Abstract : Inflammation is the body's protective reaction to injury and infection. Pain is a hallmark of inflammation and can be either protective or detrimental during acute or chronic phase. Macrophages play a chief role in the pathogenesis of pain and have bilateral communications with nociceptors, the specialized primary sensory neurons that sense pain. Macrophages 'talk to' nociceptors by releasing pro-inflammatory mediators (e.g. pro-inflammatory cytokines) that induce pain via direct activation of nociceptors. Macrophages also 'listen to' nociceptors, by which nociceptors secrete neuropeptides and chemokines which act on macrophages. Activation of toll-like receptors (TLRs) in nociceptors releases CCL2, activating macrophages and potentiating pathological pain. Emerging evidence also points to a pro-resolution role of macrophages in inflammation and pain. Macrophage GPR37 is activated by neuroprotectin D1, a specialized pro-resolving mediator (SPM) and resolves inflammatory pain via phagocytosis and production of IL-10 that inhibits nociceptors. Macrophage-nociceptor interactions are also mediated by microRNAs and microRNA-containing exosomes in chronic pain. Notably, extracellular microRNAs (e.g. let-7b and miR-711) can directly bind and activate nociceptors. Targeting macrophage-nociceptor interactions will help to control inflammation and pain.